Global supply chain restructuring towards achieving a low-carbon procurement of mineral resources for metal production - Keitaro Maeno; Shohei Tokito; Ryosuke Yokoi; Shigemi Kagawa (Resources, Environment and Sustainability)
To reduce embodied CO2 emissions in producing metals for which rapid demand growth is expected due to their critical role in decarbonization, it is essential for metal industries worldwide to establish a low-carbon procurement structure of mineral resources as raw materials for their production activities. This study explored the CO2 reduction potential by shifting the sourcing partners of mineral resources for metal production towards a low-carbon procurement structure, considering the structural changes in global supply chains (GSCs) (i.e., GSC restructuring) triggered by these shifts. In this process, we applied a multi-regional input output framework in an extended way to model the GSC restructuring based on physical transactions of mineral resources internationally traded in GSCs. From the results focusing on the restructuring of GSCs of the Japanese industries towards the low-carbon procurement of iron and copper ores revealed a CO2 reduction potential of the GSC restructuring by approximately -40% of CO2 emissions embodied in the production of both relevant mineral resources induced in the GSCs. Furthermore, by comparing the restructuring in GSCs of the Japanese, German, USA, and Chinese industries, we highlighted differences in the significance of the CO2 reduction potential of GSC restructuring in each GSC. Finally, we demonstrated the GSC restructuring formulated in this study has a large contribution to reducing scope3-CO2 emissions of metal production in the relevant GSCs, and provided effective policy suggestions for governments in countries that rely on outsourcing for mineral resources based on our findings.